EXPLORING RISK-TAKING PROPENSITY AND FEAR OF TAKING COVID-19 VACCINE ON INTENTION TO TAKE COVID-19 VACCINE AMONG NURSING STUDENTS OF THE UNIVERSITY OF IBADAN, NIGERIA - Uye, Emmanuel E.; Roberts, Enyelunekpo R.; Omoyeni, Ayomikuleyin O.; Olapegba, Peter O. (African Journal of Social and Behavioural Sciences, 2022)
The COVID-19 pandemic has affected the whole world and nearly every facet of human endeavours. This has necessitated government sourcing for and encouraging her citizens to take vaccine against contracting the virus and spreading it. This study was conducted to investigate factors influencing intention to take COVID-19 vaccine among nursing students. The study adopted cross-sectional survey using three instruments: General Risk-Taking Propensity, Fear of Taking COVID-19 vaccine, and Intention to Take COVID- 19 Scale for data collection. Purposive and convenience sampling techniques were used to select nursing students and 200 participants, respectively, for the study. Three hypotheses were tested using zero-ordered correlation and standard multiple regression analysis at p<.05 level of significance. The result revealed that risk-taking propensity and fear of taking COVID-19 vaccine significantly correlated with intention to take COVID-19 vaccine among nursing students. Furthermore, risk-taking propensity and fear of taking COVID-19 vaccine independently predicted intention to take COVID-19 vaccine. The study concludes that risktaking propensity and fear of taking COVID-19 vaccine are robust predictors of intention to take COVID-19 vaccine among nursing students of the University of Ibadan. It is recommended that training and seminars should be organized for nursing students on COVID-19 vaccine protocol in order to develop positive attitudes and have adequate knowledge on COVID-19 vaccine.